2021
DOI: 10.3892/mco.2021.2414
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumor‑infiltrating lymphocytes in estrogen receptor‑positive and human epidermal growth factor receptor 2‑negative breast cancer

Abstract: Tumor-infiltrating lymphocytes (TILs) are a significant prognostic factor in triple-negative breast cancer. However, the clinicopathological significance of TILs in estrogen receptor (ER)-positive and human epidermal growth factor receptor 2 (HER2)-negative breast cancer remains unclear. The purpose of the present study was to evaluate the role of TILs in the prognosis of ER-positive and HER2-negative breast cancer. A total of 65 consecutive patients with ER-positive and HER2-negative breast cancer were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
8
1
Order By: Relevance
“…For luminal-HER2 negative included cases, TILs do not appear to have a significant correlation with pCR, as has been found in many previous studies [30,31] and in a meta-analysis performed by Gao and his colleagues [32]. In contrary to the findings of most of the reviewed studies, we were unable to find a significant association between TILs and pCR in TNBC [33,34].…”
Section: Relation Between Luminal Subtypes Tils and Naccontrasting
confidence: 74%
See 1 more Smart Citation
“…For luminal-HER2 negative included cases, TILs do not appear to have a significant correlation with pCR, as has been found in many previous studies [30,31] and in a meta-analysis performed by Gao and his colleagues [32]. In contrary to the findings of most of the reviewed studies, we were unable to find a significant association between TILs and pCR in TNBC [33,34].…”
Section: Relation Between Luminal Subtypes Tils and Naccontrasting
confidence: 74%
“…In regard to the relationship between tumor-infiltrating CD20 B cells and neoadjuvant chemotherapy, previous studies were inconclusive [ 29 , 30 ]. Some studies found that the mean of CD20 B cells in tumors was not significantly associated with chemotherapy effect [ 31 , 32 ]. However, a link has been found between B cell infiltration and poor prognosis in a recent clinical study [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…We then analyzed the influence of the peritumoral infiltrate on the prognostic value of nuclear receptors. Although the prognostic value of TIL levels in the ER-negative/Her2-negative breast cancer population is well known, the impact of immune infiltration on the prognosis value of NRs was never investigated before [ 53 , 54 , 55 ]. ERα (and steroid hormone receptor expression in general) is known to be favorable concerning OS [ 56 , 57 , 58 ] in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Stromal TILs were quantified on hematoxylin and eosin sections of tumor according to the guidelines of the International TILs Working Group [ 41 ]. The stromal TILs count was categorized into three grades: low (0–10%), intermediate (10–40%), or high (40–90%) [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%